Maintenance of behaviour change after a 12-week mHealth lifestyle programme for young adults. - Margaret Allman-Farinelli; Kevin McGeechan; Elizabeth Denney Wilson; Mark Harris (Frontiers Media S.A., 2015)
Background: While behaviour change programmes for weight management may be successful short-term, sustained change is critical to halt incident obesity and maintain health. Aim: The aim of this study was to assess maintenance of lifestyle behaviour changes, six months after cessation of a randomised controlled trial of a 12-week mHealth programme for the prevention of weight gain in overweight 18 to 35-year-olds. Methods: Two hundred and fifty participants were randomized to the 'TXT2BFiT' trial and at 12-weeks significant weight loss and improvements in nutrition and physical activity were observed in the intervention group. The programme included brief telephone coaching for goal setting and review, educational and motivational text messages tailored to stage-of-change, email, apps for self-monitoring nutrition and physical activity behaviours, and website with additional resources. At 12 weeks subjects continued in treatment or control group for a further six months. Subjects in the treatment group received two brief coaching telephone calls over the six months and monthly text message and email. The control group were not contacted during maintenance except for assessments. Subjects completed online questionnaires at beginning and completion of maintenance phase that included questions on body weight, fruit intake, vegetable intake, consumption of sugar-sweetened beverages and energy-dense take-away foods and activity patterns. Differences between groups during the intervention and after the six months maintenance phase were analysed using PROC Mixed Models (weight and physical activity) and PROC GLIMMIX (diet behaviours) and adjusted for gender and recruitment method in SAS (SAS Institute, Cary, NY. US). Results: During the six months of maintenance the treatment subjects lost further weight such that at nine months the difference between the intervention and control groups was 4.3 kg (SE 1.3) P<0.001 (having been 3.7 kg (SE 1.2) at 12 weeks after the programme). At nine months, intervention participants had higher odds of eating more fruit and vegetables (Odds ratios=3.2 (95% CI: 1.4, 7.3) and 3.4 (1.4, 8.0), respectively, P<0.01 for each), drinking less sugar-sweetened beverages (2.7 (1.3, 5.9), P<0.01), and eating less take-away foods (3.2 (1.4, 7.4), P<0.01). Physical activity was not different between groups. Conclusions: Young adulthood is a period of rapid weight gain but this group are hard to reach for health promotion. Despite the relatively low intensity of the TXT2BFiT programme, behaviours were maintained during the six months following the intervention. mHealth shows promise to deliver intervention with wide reach and low cost.